2013
DOI: 10.1088/0960-1317/23/3/035035
|View full text |Cite
|
Sign up to set email alerts
|

Plasma extraction by centrifugo-pneumatically induced gating of flow

Abstract: We present a novel valving mechanism to implement plasma extraction from whole blood on a centrifugal microfluidic ‘lab-on-a-disc’ platform. The new scheme is based on pressure-induced deflection of a liquid membrane which gates the centrifugally driven flow through a microfluidic structure. Compared to conventional concepts such as capillary burst valves, siphons or sacrificial materials, the valving structure presented here is represented by a compact, small-footprint design which obviates the need for (loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…For instance, sample pre-treatment units (e.g. plasma separation unit 50,51 ) or downstream applications (such as array technologies or immuno-PCR for the analysis of multiple targets in a sample) can also be readily integrated into the design scheme. We are further investigating the prestorage of immunoreagents and washing buffers into stick-packs 52 , which will obviate the need for the dispensing of reagents, thereby making the developed IA highly-simplified for the end-users.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, sample pre-treatment units (e.g. plasma separation unit 50,51 ) or downstream applications (such as array technologies or immuno-PCR for the analysis of multiple targets in a sample) can also be readily integrated into the design scheme. We are further investigating the prestorage of immunoreagents and washing buffers into stick-packs 52 , which will obviate the need for the dispensing of reagents, thereby making the developed IA highly-simplified for the end-users.…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that the developed MCIA shows optimum performance with a 15 min incubation time for the formation of the sandwich immune complex and by applying two successive washing steps with washing buffer (see supplementary Figure S2A Table S2). The EC 50 respectively. The sensitivity of the automated LabDisk-based MCIA was observed to be slightly lower than that of the manual MCIA in diluted human serum, which might be due to the lower sensitivity of non-integrated chemiluminescent detector being employed in the LabDisk player in comparison to the optical detector in commercial MTP reader.…”
Section: Developed Labdisk-based Crp Mciamentioning
confidence: 99%
“…The use of serum, as demonstrated in this work however, requires prior serum separation from whole blood, which may impede use at the point-of-care. Nevertheless, several concepts for serum or plasma separation [74][75][76] have already been demonstrated on the centrifugal microfluidic platform, which could be combined with the LDAA in the future. For DNA extraction of samples with a high background of human DNA (such as whole blood), removal of the human DNA with a selective cell lysis and human DNA digestion 77 might be required to increase the bacterial DNA extraction yield or decrease non-specific amplification in subsequent PCRs 78 .…”
Section: Discussionmentioning
confidence: 99%
“…With a fixed sample volume of 40 ll, the volume of the RBC collection chamber determines the maximum hematocrit that can be processed. We designed the RBC collection chamber to hold 25.9 ll thus covering 64.75% of the total sample volume with a buffer of 4.75% above the maximum shock interface, which reduced the risk of resuspending red blood cells due to Euler forces during frequency changes at high hematocrit levels, as reported in the literature (Burger et al, 2013 andAmasia andMadou, 2010). Yet, siphon priming by pneumatic actuation allows for continuous operation at high rotational frequencies-also during siphon priming and plasma collection.…”
Section: Simulation and Fabricationmentioning
confidence: 99%
“…Hence, the speed of such a plasma separation process is always limited by the minimum rotational frequency to open the valve. With this method, a 5 ll whole blood sample with a hematocrit in the physiological range was processed within 120 s (Burger et al, 2013).…”
Section: Introductionmentioning
confidence: 99%